2016
DOI: 10.1186/s40064-015-1654-7
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic contrast-enhanced breast MRI at 7T and 3T: an intra-individual comparison study

Abstract: The aim of this study is to compare the current state of lesion identification, the BI-RADS classification and the contrast-enhancement behavior at 7T and 3T breast MRI in the same patient group. Twenty-seven patients with thirty suspicious lesions were selected for this prospective study and underwent both 7T and 3T MRI. All examinations were rated by two radiologists (R1 and R2) independently on image quality, lesion identification and BI-RADS classification. We assessed sensitivity, specificity, NPV and PPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…A recent study by Menezes et al that lesion identification, assigned BI‐RADS classification, and the contrast‐enhancement behavior at 7T and 3T breast MRI in the same patient group, had similar results. They authors concluded that 7T MRI of the breast allows BI‐RADS conform analysis yet technical improvements, such as acquisition of T 2 ‐weighted sequences and adjustment of B 1 + field inhomogeneity, are still necessary . A recent study by Bogner et al showed that B 0 images derived with DWI can be used to provide T 2 ‐weighted images and thus this limitation of clinical breast MRI at 7T has been overcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Menezes et al that lesion identification, assigned BI‐RADS classification, and the contrast‐enhancement behavior at 7T and 3T breast MRI in the same patient group, had similar results. They authors concluded that 7T MRI of the breast allows BI‐RADS conform analysis yet technical improvements, such as acquisition of T 2 ‐weighted sequences and adjustment of B 1 + field inhomogeneity, are still necessary . A recent study by Bogner et al showed that B 0 images derived with DWI can be used to provide T 2 ‐weighted images and thus this limitation of clinical breast MRI at 7T has been overcome.…”
Section: Introductionmentioning
confidence: 99%
“…They authors concluded that 7T MRI of the breast allows BI-RADS conform analysis yet technical improvements, such as acquisition of T 2 -weighted sequences and adjustment of B 1 1 field inhomogeneity, are still necessary. 42 A recent study by Bogner et al 43 showed that B 0 images derived with DWI can be used to provide T 2 -weighted images and thus this limitation of clinical breast MRI at 7T has been overcome. Nevertheless, there are still challenges and due to the limited availability of ultrahigh-field scanners worldwide, the current use of MRI of the breast at 7T in clinical practice is still limited.…”
mentioning
confidence: 99%
“…In terms of diagnosis and tumor detection, 7-Tesla MRI has been described as a safe procedure in breast cancer [51]. 3D chemicalexchange saturation transfer imaging (CEST) showed that magnetization transfer asymmetry values were positively correlated with tumor proliferation and that this index might become a biomarker of high interest in breast tumor characterization [52].…”
Section: Discussionmentioning
confidence: 99%
“…This information was applied for cancer detection and checking the tumour response to treatment. Although breast MRS started from phosphorus atoms, today because of the higher sensitivity of 1H-MRS in comparison with 31P-MRS, there is increasing interest in breast cancer research by means of hydrogen 1H-MRS. Several studies have shown that the signal of tCho can be observed in malignant lesions; however, it is not visible in normal tissues or benign tumours [186][187][188][189][190].…”
Section: Breast Mrsmentioning
confidence: 99%